UTILIZATION OF WASTE CLAY BRICKS POWDER AS A PARTIAL CEMENT REPLACEMENT IN CONCRETE - Jimoh, Lukmon O.; Aguwa, J. I.; Oritola, S. F. (FUDMA JOURNAL OF SCIENCES, 2025)
Cement production emits carbon dioxide (CO2), contributing to global greenhouse gas emissions. Waste Clay Bricks (WCB) are abundant in Minna and often disposed of in landfills, causing environmental pollution. This study investigates the pozzolanic properties of WCB and their effect on concrete strength. Pozzolanic reactivity was assessed using the Strength Activity Index (SAI) per ASTM C618. X-ray fluorescence (XRF) analysis determined the oxide composition of WCB powder, confirming its suitability as a pozzolanic material. Concrete specimens were prepared with 5%, 10%, 15%, and 20% WCB as partial cement replacements for grade 25 concrete, targeting a mean strength of 33.20 N/mm² at a 0.5 water/cement ratio. Aggregate tests, including sieve analysis, natural moisture content, specific gravity, and Bulk density, were conducted per British Standards. The oxide composition met ASTM C618 requirements, with SiO2, Al2O3, and Fe2O3 totalling 94%. WCB improved workability, with slump values of 64 mm, 71 mm, and 87 mm for 5%, 10%, and 15% replacements. Durability tests indicated increased permeability and shrinkage at higher WCB content. Compressive strength improved over time, reaching 18.5 N/mm² at 7 days, 22.4 N/mm² at 14 days, and 24.8 N/mm² at 21 days. At 28 days, 5% WCB achieved 25.41 N/mm², close to the control’s 26.07 N/mm². Despite these improvements, higher replacement levels reduced strength. The findings suggest WCB can be utilized as a partial cement replacement, but its use should be limited to 5% for grade 25 concrete to maintain structural integrity and durability.